Understanding Underage Alcohol Consumption: Exploring Motivations, Influences, and Impacts Among Students - Nakhma'Ussolikhah; Lina Marliana; Hara Permana; Muslimah; Rizky Isnaeni Fajri (Ilmu Inovasi Nusantara, 2024)
This research discusses the negative behavior of students in consuming alcoholic drinks. The reason for consuming alcoholic drinks is to maintain solidarity with middle- aged friends and to forget the various problems they are facing. The subjects of this research consisted of 1 primary subject and 3 secondary subjects, the main informant is a class IX C student and supporting informants consist of 2 guidance and counseling teachers and a friend of the main informant who knows the behavior of consuming alcoholic drinks. This research is qualitative phenomenological research. Data collection techniques using interviews, observation and documentation. The data analysis technique used was source triangulation. The results of this study show changes in negative behavior in underage students who consume alcoholic drinks starting when the children are under 15 years of age, they consume alcoholic drinks in quiet places. Contributing factors include low self-esteem and the influence of social interactions with friends, family disharmony, low economy and low formal and non-formal education. The effects of this behavior range from having a dizzy head and a faster heartbeat, which can affect poor learning achievement at school. Guidance and Guidance Teachers can provide individual counseling services using Behavioristic techniques